Study of the role of marketing strategies in the startup project management system - Shvediuk, Iuliia (Herald of Economics, 2025)
Introduction. In todayʼs changing conditions of entrepreneurial activity, the ability of management to clearly assess the effectiveness of the management system is key important. This allows for timely adaptation to changes caused by external factors (war, political situation, socio-economic development, technological innovations), and much faster response to unstable internal factors (marketing policy, strategic management, operational management, human resource policy, accounting policy). The purpose of the article is to study the marketing strategies of IT companies and to develop practical recommendations for improving the startup project management system. Research methods. The basis of the research is general scientific and special methods: explanation, generalization, comparison, analysis, induction, deduction, integrated approach, Lean model, PEST-analysis, SMART method, Eisenhower matrix, Pomodoro method, Value Stream Mapping. Results. The content of the startup project management system and the features of startup financing were studied. “JUSTANSWER Ukraine” LLC was chosen as a case study, a Lean business model was developed and a PEST-analysis of the influence of external factors was performed. The algorithm for setting the task and delegating authority between the management and employees of the IT company was substantiated. A mechanism for forming and implementing the marketing strategy of the IT company was proposed, and practical recommendations for improving the startup project management system were developed. Prospects. Further research should contribute to the popularization and wider use of the concept of lean production management in various sectors of the economy to increase market needs and create a maximum value for the client at minimal cost of production resources. Substantiation of the key elements of the companyʼs strategic marketing system will contribute to strengthening market positions, increasing product sales and improving the quality of services. It is advisable to replace the Lean methodology for developing a mechanism for the companyʼs marketing strategy.